2017
DOI: 10.1002/pbc.26471
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine‐induced peripheral neuropathy in survivors of childhood acute lymphoblastic leukaemia

Abstract: Sixteen percent of ALL survivors had VIPN. VIPN should be increasingly recognised as a late effect of chemotherapy, as it significantly affects physical and social function quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 38 publications
3
70
4
3
Order By: Relevance
“…In the current study, we observed that impaired quadriceps strength, impaired cardiopulmonary fitness, decreased balance, and impaired peripheral nervous system integrity were associated with lower scores on the SF‐36 summary scales. This finding is concordant with previous reports among childhood cancer survivors where it was shown that self‐reported function and/or symptoms influence HRQoL, and similar to studies in other cancer survivor populations (adult and pediatric) where it was shown that reduced aerobic capacity, muscular weakness, inadequate postural control, and neuropathy influence perceived health. To our knowledge, this is the first study that has evaluated a link between fitness, peripheral nervous system integrity, and HRQoL among survivors of childhood HL.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we observed that impaired quadriceps strength, impaired cardiopulmonary fitness, decreased balance, and impaired peripheral nervous system integrity were associated with lower scores on the SF‐36 summary scales. This finding is concordant with previous reports among childhood cancer survivors where it was shown that self‐reported function and/or symptoms influence HRQoL, and similar to studies in other cancer survivor populations (adult and pediatric) where it was shown that reduced aerobic capacity, muscular weakness, inadequate postural control, and neuropathy influence perceived health. To our knowledge, this is the first study that has evaluated a link between fitness, peripheral nervous system integrity, and HRQoL among survivors of childhood HL.…”
Section: Discussionsupporting
confidence: 92%
“…While the reported incidence rates vary considerably—depending on the severity of symptoms, diagnostic criteria and concomitant use of other neurotoxic agents—most patients receiving vincristine develop some degree of sensory peripheral neuropathy at a cumulative dose of >4 mg/m 2 (Ramchandren et al, 2009; Toopchizadeh et al, 2009; Seretny et al, 2014; Lavoie Smith et al, 2015; Tay et al, 2017). …”
Section: Cancer Chemotherapy: Drug Mechanism Of Action and Metabolitesmentioning
confidence: 99%
“…Vincristine is administered in weekly intervals with a dose of 1.5 to 2 mg/m . Among the vinca alkaloids, vincristine is the most neurotoxic and patients receiving vincristine develop some degree of vincristine‐induced peripheral neuropathy (VIPN) at a cumulative dose of >4 mg/m 2 . However, recently marketed lipid‐coated or liposomal vincristine increased the safety margin and tissue penetration .…”
Section: Oncological Use Dose and Neurotoxicitymentioning
confidence: 99%